2015
DOI: 10.1039/c4ra15899g
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene ethyl phosphate as a multifunctional electrolyte additive for lithium-ion batteries

Abstract: The effects of ethylene ethyl phosphate (EEP) as a multifunctional electrolyte additive on safety characteristics and electrochemical performance of lithium-ion batteries are investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 39 publications
0
37
0
1
Order By: Relevance
“…To the best of our knowledge, this performance is more than the previous results, a comparison of this work with the latest literature has been made and the specific values are listed in Table S2 (Supporting Information). [ 42,43 ] In addition, the improvement of Li anode induced by the coadditives is also explored. The NMC//Li battery is disassembled after 100 cycles and then reassembled a new battery by replacing a fresh Li foil anode.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, this performance is more than the previous results, a comparison of this work with the latest literature has been made and the specific values are listed in Table S2 (Supporting Information). [ 42,43 ] In addition, the improvement of Li anode induced by the coadditives is also explored. The NMC//Li battery is disassembled after 100 cycles and then reassembled a new battery by replacing a fresh Li foil anode.…”
Section: Resultsmentioning
confidence: 99%
“…TMSPi 可抑制正极界面 Mn 的溶解, 而 VC 可减少负极 Mn 的 沉 积 , 因 此提 高了 电 池 在 60 ℃ 的电 化学 性 能 [102,103] . [113] , 兼具较好的阻燃性和成膜性. [8] .…”
Section: Tmspunclassified
“…[10] This issue can be resolved by substituting the hydrogen atom(s) with fluorine. [8][9] Recently, Gao et al [11] reported the use of cyclic phosphate, namely ethylene ethyl phosphate (EEP) as a flame retardant cosolvent and showed that 10 % of EEP reduces the flammability of the electrolyte by 50 %. However, the electrolyte still burns for � 65 s/g and by the definition of Xu et al [7a] (flame retardant between SET: 6-20 s/g and as nonflammable with a SET: < 6 s/ g) this molecule cannot be considered as FR.…”
Section: Introductionmentioning
confidence: 99%
“…The cyclic 1,3,2-dioxaphospholane core structure is known to enhance cycling performance by forming an effective cathode electrolyte interface (CEI) via ring opening polymerization on the NMC111 electrode surface. [11][12] Additionally, this molecule features a side chain, which can be easily modified to bear a variety of functional groups, making it a very versatile core structure. Based on previous results, we selected the pentafluoropropyl group as a side chain to further support the flame retarding properties of the phospholane core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation